Comprehending Non-Litigative Resolution of Construction Disputes Through Arbitration - Niniek Lannyati; Samian (Journal of Law, Politic and Humanities, 2025)
Construction projects are inherently complex, and involve multiple stakeholders with diverse interests and goals. The construction industry has explored the use of hybrid dispute resolution methods, such as the combination of arbitration and mediation, known as "med-arb.” However, the effectiveness of arbitration in construction disputes is not challenging. The challenge to be examined is the choice of construction dispute resolution using arbitration, which is still widely used in Indonesian projects. During the 44 years of work, the Indonesian National Arbitration Board handled more than 1000 cases. Regulation reflects the evolving dynamics and challenges faced by the Indonesian legal system and the ongoing efforts to create a more democratic and rights-respecting legal framework